Preservation of Ancient Manuscript and Transliteration of Tambo Minangkabau Surambi Alam Sungai Pagu: Web-Based Digital Literacy - Septia, Emil; Junaidi, Rohayati (Universitas PGRI Sumatera Barat, 2025)
The old text of Tambo Surambi Alam Sungai Pagu constitutes a significant cultural heritage of the Minangkabau people. This manuscript chronicles the history of the Minangkabau Rajodom, which was composed initially by hand before its publication. To save the text against deterioration and natural calamities, such as fire and flood, preservation efforts, including digitalization, are essential. Digitalization converts media from printed, audio, or video formats to establish digital document repositories. Digitalization necessitates computers, scanners, operators, media, sources, and software. This study seeks to elucidate the procedure of translating the SASP manuscript from Arabic-Malay script to Latin script utilizing the Philology approach and delineate the process of web-based digitalization of the SASP manuscript. Two research methodologies exist: the Philological research method and the digitalization approach. The philological approach encompasses the processes of transliteration or transcription. The digitization of old SASP texts involves the building of software architecture applications. The digitization of this information system employs the PhoneGap operating system. From the data analysis, the subsequent conclusions can be derived. Initially, according to Philological research, namely the translation of the SASP manuscript, there are terms inscribed in Arabic alongside the utilization of Malay, Minangkabau, and antique vocabulary. The text serves a societal purpose as a source of information regarding the genealogy of the Pagaruyung Rajodom's history. Secondly, drawing from digitalization research utilizing the PhoneGap operating system, it can be elucidated that this design constitutes a digital web application for ancient SASP manuscripts, facilitating access to comprehensive information regarding these manuscripts. The test findings indicate that this application can deliver information according to user requirements, including manuscript details in Arabic Malay script and translation. The translation and digitization of this document will serve as a resource for digital literacy for students and the community